Trade and production fragmentation : Central European economies in EU networks of production and marketing - Kamiński, Bartłomiej 1944- (Policy research working paper, 2001)
The unprecedented globalization of the production process, dividing up the value chain, has brought the integration of trade and the disintegration of production, with deep implications for the international division of labor. Have Central European economies been able to readjust their production structures to international markets? Three of them: Estonia, Hungary, and Slovakia have done especially well